Characteristics of B lymphocyte infiltration in HPV+ head and neck squamous cell carcinoma. Issue 4 (25th February 2021) - Zhang, Siwei; Wang, Bozhi; Ma, Fen; Tong, Fangjia; Yan, Bingqing; Liu, Tianyang; Xie, Huanhuan; Song, Lianhao; Yu, Siyang; Wei, Lanlan
Abstract: Human papillomavirus (HPV) is an important etiological factor of head and neck squamous cell carcinoma (HNSCC). HPV + HNSCC patients usually have a better prognosis, which probably results from the higher infiltration of B lymphocytes. This study was purposed to detect the infiltration of B lymphocyte subsets and the correlation between B lymphocyte subsets and the prognosis in HPV‐related HNSCC. In this study, 124 HPV + and 513 HPV − HNSCC samples were obtained from the Gene Expression Omnibus (GEO) database and The Cancer Genome Atlas (TCGA) database for transcriptomic analysis. Infiltration of B lymphocytes subsets was detected with 7 HPV + HNSCC and 13 HPV − HNSCC tissues through immunohistochemistry and immunofluorescence. One HPV − HNSCC sample was detected with single‐cell sequencing for chemokine analysis. In the results, the infiltration of plasma cells (CD19 + CD38 + ) and memory B cells (MS4A1 + CD27 + ) was higher in HPV + HNSCC samples. High infiltration of plasma cells and memory B cells was related to a better prognosis. High density of B lymphocytes was positively correlated with high CXCL13 production mainly from CD4 + T lymphocytes in HNSCC. These results indicated that a high density of plasma cells and memory B cells could predict excellent prognosis. CD4 + T lymphocytes might affect B lymphocytes and their subsets through the CXCL13/CXCR5 axis in HNSCC. Abstract : For the first time, we observed the infiltration and distribution of B lymphocyte subsets around HNSCC tissues by immunohistochemistry and immunofluorescence. We first discovered that the high infiltration of plasma cells (CD19 + CD38 + ) and memory B cells (MS4A1 + CD27 + ) in HPV +  HNSCC microenvironment was related to better prognosis, and CD4 + T cells could affect B lymphocyte infiltration through the CXCL13/CXCR5 axis.